2022
DOI: 10.3390/children10010088
|View full text |Cite
|
Sign up to set email alerts
|

Skin Barrier Function and Infant Tidal Flow-Volume Loops—A Population-Based Observational Study

Abstract: Background: The relationship between skin barrier- and lung function in infancy is largely unexplored. We aimed to explore if reduced skin barrier function by high transepidermal water loss (TEWL), or manifestations of eczema or Filaggrin (FLG) mutations, were associated with lower lung function in three-month-old infants. Methods: From the population-based PreventADALL cohort, 899 infants with lung function measurements and information on either TEWL, eczema at three months of age and/or FLG mutations were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 61 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…Our finding that impaired skin barrier function in infancy was associated with asthma at age 3 years is to the best of our knowledge novel. We previously reported an inverse association between impaired skin function and lower lung function by t PTEF among 899 infants at age 3 months 18 . A German study found similar TEWL values using a patch test among 95 subjects with respiratory atopy, AD and controls 49 .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Our finding that impaired skin barrier function in infancy was associated with asthma at age 3 years is to the best of our knowledge novel. We previously reported an inverse association between impaired skin function and lower lung function by t PTEF among 899 infants at age 3 months 18 . A German study found similar TEWL values using a patch test among 95 subjects with respiratory atopy, AD and controls 49 .…”
Section: Discussionmentioning
confidence: 81%
“…We previously reported an inverse association between impaired skin function and lower lung function by t PTEF among 899 infants at age 3 months. 18 A German study found similar TEWL values using a patch test among 95 subjects with respiratory atopy, AD and controls. 49 Collectively, our finding thus supports that barrier dysfunction may play a role in asthma development.…”
Section: Ta B L Ementioning
confidence: 92%
See 2 more Smart Citations
“…A lack of disease control substantially impacts the quality of life of the patients and their caregivers [ 4 ]. Lung function tests are also useful in identifying mechanisms that predispose a patient to develop asthma, among allergies and skin barrier dysfunction [ 5 ].…”
mentioning
confidence: 99%